2020
DOI: 10.1038/s41598-020-75582-9
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infections following caesarean sections at Emirati teaching hospital: Incidence and implicated factors

Abstract: The rate of delivery by caesarean sections is increasing globally and, therefore, the incidence of post-caesarean surgical site infections (SSIs) is probably also going to rise. The aim of the present study was to determine the incidence of SSIs after caesarean operations and to explore the factors associated with an increased risk of post-caesarean SSIs. A retrospective study was performed to assess all women who underwent caesarean sections from January 2016 to December 2017 at Al Ain Hospital in the United … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
2
5
1
Order By: Relevance
“…This comes in line with previous studies that showed a single dose of cefazolin antibiotic was the most frequently administered operative antibiotic prophylaxis. 23 , 24 Additionally, these latter findings agree with the recommendation of NICE clinical guidelines (2011) regarding the best antibiotic selection and time to administer antibiotic prophylaxis. 23 , 24 The study findings encourage the importance of the clinical pharmacist in making the physicians have a better compliance to the guidelines, which shows the benefit of involving the clinical pharmacist during the stewardship program.…”
Section: Discussionsupporting
confidence: 81%
“…This comes in line with previous studies that showed a single dose of cefazolin antibiotic was the most frequently administered operative antibiotic prophylaxis. 23 , 24 Additionally, these latter findings agree with the recommendation of NICE clinical guidelines (2011) regarding the best antibiotic selection and time to administer antibiotic prophylaxis. 23 , 24 The study findings encourage the importance of the clinical pharmacist in making the physicians have a better compliance to the guidelines, which shows the benefit of involving the clinical pharmacist during the stewardship program.…”
Section: Discussionsupporting
confidence: 81%
“…This finding is slightly in line with a study done in Nepal ( 7 ). However, the current finding is significantly higher than studies conducted at the global level ( 4 ), in China ( 5 ), India ( 6 ), and the United Arab Emirate ( 8 ). The difference may be caused by socio-economic variation, poor dietary behaviors, poor personal hygiene, inadequate infection control practices implemented in healthcare, such as limited hygienic practice, inadequate antibiotic prophylaxis, a lack of aseptic wound care, and non-adherence with prescribed treatments.…”
Section: Discussioncontrasting
confidence: 79%
“…The incidence rate of surgical site infection was 0.15% in China ( 5 ), 8.02% in India ( 6 ), and 12.6% in Nepal ( 7 ). In the United Arab Emirates, surgical site infection was detected in 1.4% of the women who underwent cesarean operations ( 8 ). According to a WHO study with a special focus on surgical site infection in low and middle-income countries, the pooled prevalence of surgical site infection was 11.2 per 100 surgical patients ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is a remarkable difference between the result of the current estimate of the prevalence of post‐caesarean surgical site infections in Rwanda and the prevalence of post‐caesarean SSIs in high‐income countries. For example, there was 0.4% and 5.4% post‐caesarean SSI prevalence after elective and emergency caesarean section, respectively, in Norway, 36 0.63% in Ireland, 37 1.4% in the United Arab Emirates, 38 2.7% in Canada 39 and 2.1% in Kuwait. 40 In the recent review of the global incidence of surgical site infections following caesarean section, the lowest prevalence was found in the North American region (3.87%) while the highest incidence was in the African region (11.91%).…”
Section: Discussionmentioning
confidence: 99%